Digital algorithm-guided insulin therapy in home healthcare for elderly persons with type 2 diabetes: A proof-of-concept study - Kopanz, Julia; Mader, Julia K.; Donsa, Klaus; Libiseller, Angela; Aberer, Felix; Pandis, Marlene; Reinisch-Gratzer, Johanna; Ambrosch, Gisela C.; Lackner, Bettina; Truskaller, Thomas; Sinner, Frank Michael; Pieber, Thomas R.; et al. (Frontiers in Clinical Diabetes and Healthcare, 2022)
GlucoTab@MobileCare, a digital workflow and decision support system with integrated basal and basal-plus insulin algorithm was investigated for user acceptance, safety and efficacy in persons with type 2 diabetes receiving home health care by nurses. During a three months study nine participants (five females, age 77±10 years, HbA1c 60±13 mmol/mol (study start) vs. 57±12 mmol/mol (study end) received basal or basal-plus insulin therapy as suggested by the digital system. 95% of all suggested tasks (blood glucose (BG) measurements, insulin dose calculations, insulin injections) were performed according to the digital system. Mean morning BG was 171±68 mg/dL in the first study month vs. 145±35 mg/dL in the last study month indicating a reduced glycemic variability of 33 mg/dL (standard deviation). No hypoglycemic episode <54 mg/dL occurred. User’s adherence was high and the digital system supported a safe and effective treatment. Larger scale studies are needed to confirm findings under routine care.